The Effect of Animated Videos on Knowledge and Attitudes of Elementary School Students - Kurniawati Kurniawati; Suryati Badrin; Bara Miradwiyana; Yetty Mariani Tambun (Universitas Muhammadiyah Semarang, 2026)
The behavior of consuming unhealthy snacks among schoolchildren is still high, which can reduce students’ health. One intervention to improve this behavior is providing education about knowledge and attitudes toward healthy snacks. The aim of this study was to identify the effect of healthy snack education using animated videos on knowledge and attitudes. This research used a quantitative method with a quasi-experimental pretest-posttest control group design. The sample consisted of 112 respondents, with 56 respondents in each group. The instruments used were knowledge and attitude questionnaires that had been tested for validity and reliability. The intervention included a pretest, animated video screenings, and leaflets in the intervention group, conducted twice, followed by a posttest. In the control group, the intervention included a pretest, leaflets, and a posttest. The study was conducted in two public elementary schools in West Jakarta. The analysis of independent variables between the control and intervention groups using the Mann-Whitney test showed a p-value of 0.001 for knowledge and 0.044 for attitudes. These results indicate that educational media using animated videos about healthy snacks has an effect on improving the knowledge and attitudes of elementary school students in West Jakarta.